MAKNA RUMAH TRADISIONAL KUDUS - Anisa, Anisa (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT Poespowardojo ( in Budihardjo, 1994) stated that there are two essences of house for the residences. The former essence, house is a world where the residences must develop theirselves. The later essence, house isa place which the residence must adapt to the local culture. So that, the meaning of house has a close relation with the sicial, culture and economic background of the owner. This research is focused on the ornaments of Kudus Traditional House, that right know slowly destroyed. The aim of this research is to get the meaning of the house, through discovering the residences value systems, physically or non physically. There are several value systems found at Kudus traditional house, that is: hierarchy, status symbol, gender, sacral-profane, duniawi-ukhrowi, pingitan culture, collumn meaning, and tumpangsari. Those value systems have. very close relation and also form the meaning of Kudus traditional house. The main result of this research is that the meaning of a house is very influenced by social and culture condition in Kudus, and also by the economic background of the owner. Keywords: Kudus traditional house, meaning, value system